Percepções de trabalhadores da saúde sobre o processo de acreditação hospitalar: benefícios e oportunidades de melhorias - Cavalheiro, Mariana Digieri (Universidade Federal de São Carlos, 2023)
Hospital accreditation helps healthcare institutions gain competitive advantages, enabling them to continuously develop and adapt to successive changes in the workplace while pursuing quality in the services offered to their patients. Quality is determined by seven pillars: effectiveness, efficiency, optimization, acceptability, equity, and legitimacy, which demand professional receptivity to their activities. Professionals who possess knowledge and dedication towards their roles can accomplish the objectives of the quality policy, which strives for continuous improvement to benefit all parties within the organization. This study aimed to analyze the perception of healthcare workers regarding hospital accreditation to identify the benefits, challenges, and opportunities for improving work processes and healthcare quality. It was a descriptive-exploratory field study with a qualitative-quantitative approach. The Hospital Accreditation Process Perception Assessment (HAPPA) tool was designed with Likert scale items encompassing topics corresponding to ONA's (National Accreditation Organization) levels I and II along with open-ended questions that was formed and applied in person to 200 healthcare workers at an oncology referral hospital in the central-west region of São Paulo State. The institution has around 2,000 employees working various shifts and hours. Inclusion criteria were: being a hospital worker at all levels of education, functional literacy, and at least six months of work experience. The results showed that workers perceived accreditation as important, but expressed a need for improvement and greater professional recognition. Benefits of accreditation include improving customer satisfaction, standardizing procedures, nurturing a culture of safety, and providing opportunities for training enhancement. The challenges and difficulties indicate the necessity of collaborating among team members, having appropriate staffing for safe care delivery, and sustaining the changes made. These elements highlight the importance of complementary strategies to certification, such as continuing education - a possibility for updating professionals; aligning work processes; developing interpersonal and interprofessional relationships and collaborative practices and strengthening the organizational culture; and shared management, "giving a voice" to workers and making them aware of the importance of accreditation in the search for improvements in the quality of care, with a view to greater adherence and participation. In conclusion, the results of this study offer support for planning, since the difficulties pointed out and the need to promote the engagement of all the actors working in the institution are extremely important for improving hospital accreditation processes, through the development and involvement of the team. Additionally, the APPAH has undergone restructuring and improvement to integrate ONA III-related aspects. It can be distributed and utilized in all hospital institutions, regardless of their current certification level, to gather data and enhance staff awareness.
Perceptions of health workers about the hospital accreditation process: benefits and opportunities for improvement
Keywords: Acreditação Hospitalar; Pessoal de saúde; Equipe de assistência ao paciente; Educação permanente; Gestão da qualidade em saúde; Administração em saúde; Hospital accreditation; Health personnel; Patient care team; Permanent education; Quality management in health; Health administration; CIENCIAS DA SAUDE::ENFERMAGEM